2013
DOI: 10.7314/apjcp.2013.14.11.6529
|View full text |Cite
|
Sign up to set email alerts
|

Very Young Breast Cancer in a Referral Center in Tehran, Iran: Review of 55 Cases Aged 25 or Less throughout 33 Years

Abstract: Background: Breast cancer is mostly the disease of postmenopausal women but very young affected women are seen more than occasionally in developing countries. We reviewed our cases of very young breast cancer in order to help in better understanding of such cases. Materials and Methods: The records of patients 25 years of age or less who had been admitted for breast cancer surgery in the Cancer Institute of Tehran from 1979 to 2012 were reviewed and relevant data were extracted. Results: From 5,265 cases of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
0
13
2
Order By: Relevance
“…The cut off age limit to designate the patient as young is different and most of the series treating this subject have examined breast carcinoma in young women under 35 [4]. Few series [4,[6][7][8][9] have addressed the topic of breast cancer occurring in women in their teens or early 20s. These studies have revolved around limited number of cases with the largest series to date by Alipour S et al [9] in which 55 women were evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cut off age limit to designate the patient as young is different and most of the series treating this subject have examined breast carcinoma in young women under 35 [4]. Few series [4,[6][7][8][9] have addressed the topic of breast cancer occurring in women in their teens or early 20s. These studies have revolved around limited number of cases with the largest series to date by Alipour S et al [9] in which 55 women were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Few series [4,[6][7][8][9] have addressed the topic of breast cancer occurring in women in their teens or early 20s. These studies have revolved around limited number of cases with the largest series to date by Alipour S et al [9] in which 55 women were evaluated. No Tunisian series of breast cancer before 25 years-old are available, which inspired the current retrospective study of a series including 25 patients of early onset breast cancer diagnosed under the age of 25 years over a period of 21 years.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with this type of breast cancer are typically less than 40 years old (16). This kind of breast cancer is associated with a worse prognosis and does not respond to typical treatments and has the morphology of epithelial cells with substantial invasion (17). In this study, MDA-MB 231 cell line was used to evaluate this type of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In Asian women, breast cancer presents relatively earlier compared to the Western countries and the incidence of breast cancer among young women under 40 years of age is relatively high. Recent studies from Asia have shown that 11% to as high as 28% of all breast cancers are diagnosed in women under 40 years of age and the incidence in young women is increasing in the Asian population [1][2][3][4][5][6][7][8][9][10]. Various studies have shown that women who develop breast cancer at a younger age (< 40 years) tend to have more aggressive disease with worse clinicopathological features.…”
Section: Introductionmentioning
confidence: 99%
“…Percentage of young Asian women with risk factors for breast cancer is signi cant [1][2][3][4][5][6][11][12][13].…”
Section: Introductionmentioning
confidence: 99%